Dog Wool Microparticles/Polyurethane Composite for Thermal Insulation - Claudivan da Silva, Francisco (Polymers (Basel), 2020)
A polyurethane (PU)-based eco-composite foam was prepared using dog wool fibers as a filler. Fibers were acquired from pet shops and alkaline treated prior to use. The influence of their incorporation on the PU foams’ morphological, thermal, and mechanical properties was investigated. The random and disorganized presence of the microfibers along the foam influence their mechanical performance. Tensile and compression strengths were improved with the increased amount of dog wool microparticles on the eco-composites. The same occurred with the foams’ hydration capacity. The thermal capacity was also slightly enhanced with the incorporation of the fillers. The fillers also increased the thermal stability of the foams, reducing their dilatation with heating. The best structural stability was obtained using up to 120 °C with a maximum of 15% of filler. In the end, the dog wool waste was rationally valorized as a filler in PU foams, demonstrating its potential for insulation applications, with a low cost and minimal environmental impact.